2013
DOI: 10.1371/journal.pone.0056181
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Multiple Facets of Glycogen Metabolism in a Murine Model of Pompe Disease

Abstract: Pompe disease, also known as glycogen storage disease (GSD) type II, is caused by deficiency of lysosomal acid α-glucosidase (GAA). The resulting glycogen accumulation causes a spectrum of disease severity ranging from a rapidly progressive course that is typically fatal by 1 to 2 years of age to a slower progressive course that causes significant morbidity and early mortality in children and adults. The aim of this study is to better understand the biochemical consequences of glycogen accumulation in the Pomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 14 publications
4
34
0
Order By: Relevance
“…In the desiccated and ethanol treated liver tissue samples the triplet of bands due to glycogen (1154, 1080, 1035, 1022 cm −1 ) appeared strong in the spectra but were weak in the wet spectra and altered to a broad band feature in the formalin fixed tissues. Establishment of glycogen levels is important for the diagnosis of many diseases [ 35 , 36 ]. Clearly the spectra indicate that formalin fixation has some effect on glycogen chemistry in tissues.…”
Section: Resultsmentioning
confidence: 99%
“…In the desiccated and ethanol treated liver tissue samples the triplet of bands due to glycogen (1154, 1080, 1035, 1022 cm −1 ) appeared strong in the spectra but were weak in the wet spectra and altered to a broad band feature in the formalin fixed tissues. Establishment of glycogen levels is important for the diagnosis of many diseases [ 35 , 36 ]. Clearly the spectra indicate that formalin fixation has some effect on glycogen chemistry in tissues.…”
Section: Resultsmentioning
confidence: 99%
“…PD is a monogenic disease that is caused by GAA deficiency and dysregulation of glycogen metabolism . We hypothesized that glycogen accumulation may affect the cellular metabolism, including glycolysis and oxidative phosphorylation (OXPHOS).…”
Section: Introductionmentioning
confidence: 99%
“…Pompe disease, also known as Glycogen Storage Disease (GSD) type II, is caused by deficiency of lysosomal acid α-glucosidase (GAA). Muscle lysates collected from GAA -/mouse strains had elevated GS, glycogenin, hexokinase, and G6P, and decreased GP activity in the absence of AMP [44]. It has been shown that recombinant human GAA (rhGAA) can improve the clinical outcomes of Pompe disease with variable results [45].…”
Section: Components In Signal Transduction Pathwaysmentioning
confidence: 99%